2016
DOI: 10.15740/has/ijpp/9.1/133-136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium silicate and need based nitrogen on pests management in aerobic rice (Oryza sativa L.)

Abstract: The dynamic and severity of pests attack has shifted with the adaptation and spread in rice. Excessive use of chemicals for pest and diseases control in agriculture is known to degrade the environment. Use of silicon (Si) and nitrogen (N) management in aerobic rice involves a proper choice and blend of compatible tactics to keep the pests at low level. The present investigations were done to know the effect of calcium silicate and nitrogen on the pest infestation in aerobic rice. The results revealed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Silicon (Si) is the second most abundant element in the earth’s crust and its effect on organisms may be different, serving as a cellular chemical element or providing a natural morphological modification [ 7 , 8 , 9 , 10 , 11 ]. As a cellular chemical element, it plays an important role in the mineral nutrition of plants, aiding development by increasing the organism’s biomass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon (Si) is the second most abundant element in the earth’s crust and its effect on organisms may be different, serving as a cellular chemical element or providing a natural morphological modification [ 7 , 8 , 9 , 10 , 11 ]. As a cellular chemical element, it plays an important role in the mineral nutrition of plants, aiding development by increasing the organism’s biomass.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, calcium silicate is also used to provide a natural morphological modification in insects, that is, when ingested occurs damage to the oral apparatus of pests that attack plants, due to its crystalline physical structure [ 9 , 12 , 13 , 14 , 15 , 16 ]. Previous studies have reported reduced insect feeding on turf treated with calcium silicate, as well as others that show that calcium silicate enhances resistance of sugarcane to the African talk borer Eldana saccharina [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are used in the biomedical field, where they have shown great biocompatibility, antibacterial activity, and bioactivity; the latter plays a fundamental role in the regeneration and healing of tissues, and the performance of calcium silicate materials is largely attributable to their bioactivity [8][9][10]. It has also been widely used in the production and cultivation of different plant crops [11][12][13][14][15]. The high compatibility of calcium silicate and mushrooms when compared to other supplementation materials has attracted attention towards its supplementation in several crops.…”
Section: Introductionmentioning
confidence: 99%